Mendidik Anak Diera Digital: Tantangan dan Solusinya - Sulastya Ningish; Nurul Aini MM Sodik; Maryam Adam; Elsya Usman; Siti Fadila Rajulali (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The development of digital technology has brought about significant changes ini parenting patterns and the learning process for early childhood. Children are now familiar with using devices for lpay, learning, and intraction, requiring parents and techers to have the ability to guide their childrens appropriate use of technology. Although technology facilitates access to information, unsupervised use can trigger various problems, such as screen addiction, reduced sosial interaction, exposure to age-inappropriate content, and decreased concentration. Therefore, supervision and guidance are crucial elements ini educating children in the digital age. Various studies confirm that regulating device usage time, implementing firm rules, active guidance, and instilling character values are essential for children to use technology in a healthy and responsible manner Synergy beyween parents and schools, along with improving digital literacy, are key factors in ensuring that technology provides safe and positive benefits for childrens cognotive, social, emotional, morality, and physical-motor development. A comprehensive approach is necessary for children to develop optimally amidst the rapid development of the digital world.